Normocytic Normochromic Anemia Revealed an Early Onset Hashimoto’s Hypothyroidism in an Infant: A Case Report - Manal Mustafa Khadora; Maysa Saleh; Rawah Idres; Sura Ahmed Al-Doory; Mahmoud Ahmed Radaideh (Dubai Medical Journal)
Autoimmune thyroiditis is very rare etiology of primary hypothyroidism in infancy. Hypothyroidism has a wide range of clinical presentation, from subclinical hypothyroidism to overt type. It is unclear what pathological mechanisms connect thyroid function and erythropoiesis or how thyroid disease can contribute to anemia. We report a 12-month-old infant who presented with anemia associated with early onset of overt autoimmune thyroiditis. The peculiarity of our case enables us to draw attention of physician to consider acquired hypothyroidism in the differential diagnosis of unexplained anemia even if the neonatal screening is normal and congenital hypothyroidism is a remote possibility.